Shen-Yuan-Dan Capsule Attenuates Verapamil-Induced Zebrafish Heart Failure and Exerts Antiapoptotic and Anti-Inflammatory Effects via Reactive Oxygen Species–Induced NF-κB Pathway - Li, Sinai; Liu, Hongxu; Li, Yue; Qin, Xiaomei; Li, Mengjie; Shang, Juju; Xing, Wenlong; Gong, Yanbing; Liu, Weihong; Zhou, Mingxue (Frontiers in Pharmacology, 2021)
Background: Heart failure (HF) is the end stage of ischemic cardiovascular diseases; nonetheless, safe and effective therapeutic agents for HF are still lacking, and their discovery remains challenging. Our previous studies demonstrated that Shen-Yuan-Dan Capsule (SYDC), a hospital preparation of traditional Chinese herbal, effectively protected ischemic injury in cardiovascular diseases. However, its therapeutic effects and possible mechanisms on HF remain unclear. Methods: A zebrafish HF model treated with verapamil was developed to assess the therapeutic effect of SYDC on HF zebrafish. Zebrafish were administered with SYDC and digoxin (positive control) by direct soaking. After drug treatment, zebrafish were randomly assigned to the visual observation and image acquisition using a Zebralab Blood Flow System. The reactive oxygen species (ROS), MDA, and SOD levels were determined by fluorescence signal detection, TBA, and WST-8 methods. RT-PCR determined the mRNA expressions of Caspase-3, Caspase-1, Bcl-2, Bax, IL-1β, NF-κB, and TNF-α. Results: SYDC significantly inhibited the levels of heart dilatation and venous congestion and markedly increased the levels of cardiac output, blood flow dynamics, and heart rates in HF zebrafish (p < 0.05, p < 0.01, and p < 0.001). Moreover, SYDC also significantly decreased the levels of MDA and ROS and increased the level of SOD in HF zebrafish. The RT-PCR results revealed that SYDC decreased the expression of Caspase-1, Caspase-3, Bax, IL-1β, NF-κB, and TNF-α but increased the expression of Bcl-2 in HF zebrafish (p < 0.05, p < 0.01, and p < 0.001). Conclusions: SYDC improved the heart function in verapamil-induced HF zebrafish and alleviated inflammation and apoptosis by inhibiting the ROS-mediated NF-κB pathway.